Design engineering - Cather, Harry
A core text for first year modules in Design Engineering offering student-centred learning based in real-life engineering practice. Design Engineering provides all the essential information an engineering student needs in preparation for real-life engineering practice. The authors take a uniquely student-centred approach to the subject, with easily accessible material introduced through case studies, assignments and knowledge-check questions. This book is carefully designed to be used on a wide range of introductory courses at first degree and HND level. The interactive style of the book brings.